PENGARUH PERAYAAN TRADISI BUDAYA â€œPER-PERANâ€ PASCA LEBARAN DALAM MENINGKATKAN PENDAPATAN MASYARAKAT PESISIR DESA BANDARAN - Suhaimi; Nur Jamilah (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2022)
Culture and the economy essentially have an equal position and mutually support one another. Customs or culture in the country of Indonesia vary according to the tribe in which the culture appears. One of the cultures and customs inherited from our ancestors that is still going well and continues to be carried out by the community today is the "PER-PERAN" culture. In this celebration, the people of the airport village for two consecutive days will hold a procession around the village. In Increasing the Income of Coastal Communities in Bandaran Village. The method in this research is qualitative with a population of all the Bandaran village communities and the sample is the Bandaran people who trade or participate in traditional per-role celebrations. The techniques used are interviews, observation and document review. The results of the study show that the influence of per-role in increasing the income of the airport community varies according to the type of merchandise sold in per-role cultural celebrations. The influence is enormous for traders of clothes, drinks/snacks, cakes, basic necessities. For food traders, it has a negative effect because traders do not sell during the celebration. Unlike the toy dealers, they only get a very small influence from the celebration of each role almost like an ordinary day. Delman drivers and pedicab drivers each year get a decrease but increase 3 times ipa from normal days.